Bleeding predictors in acute coronary syndrome: does the age or clinical presentation matters?. (26th April 2021) - Marques Pires, C; Campos, I; Medeiros, P; Flores, R; Mane, F; Azevedo, P; Galvao Braga, C; Pereira, MA; Gaspar, A
Abstract: Funding Acknowledgements: Type of funding sources: None. INTRODUCTION: Bleeding is a quite common non-cardiac complication of acute coronary syndrome (ACS) and is associated with a negative prognosis impact. AIMS: To determine the predictors of inhospital major bleeding (IHMB) in ACS and to evaluate whether they differ according to age and clinical presentation. METHODS: A multicentric retrospective study which analysed 25524 patients(pts) with ACS, 25141 without and 383 with IHMB. By multivariate analysis, we determined IHMB predictors and evaluated the differences between age groups (<80 years; ≥80 years) and clinical presentation- ST elevation myocardial infarction (STEMI) or non-ST elevation ACS (NSTEACS). RESULTS: By multivariate analysis we found 15 significant IHMB predictors (pvalue < 0, 05): age≥75years, hypertension, previous angina, pulmonary disease, previous bleeding, atypical presentation (without pain), cardiac arrest, admission heart rate (HR)>100bpm, Killip4 at admission, ST-elevation, admission haemoglobin (Hb)<10g/dL, aspirin or Vitamin K antagonist (VKA) or ivabradine as previous medication and glycoprotein IIb/IIIa inhibitors (GPIIb/IIIa) use. Then, we made a sub-analysis in STEMI pts which revealed that IHMB predictors of pts <80 years were: female gender, age≥75years, chronic kidney disease (CKD), active neoplasm, previous bleeding, atypical presentation, cardiac arrest, admission HR > 100bpm, Killip IV on admission and GPIIb/IIIa use. By contrast, IHMB predictors of pts with ≥80 years were: valvular disease, atypical presentation, aspirin as previous medication and GPIIb/IIIa use. Finally, we made a sub-analysis in NSTACS pts which revealed that IHMB predictors of pts <80years were: previous angina, CKD, previous bleeding, cardiac arrest, Killip≥2 at admission, admission Hb < 10g/dL and VKA as previous medication. Conversely, IHMB predictors of pts with ≥80 years were previous bleeding, cardiac arrest and absence of normal QRS. In addition, by multivariate analysis we found that IHMB had an impact on inhospital mortality (OR = 2, 2;pvalue < 0, 001), however, by Cox regression there wasn't an impact on 1-year mortality. CONCLUSION: This study suggests that IHMB has impact on inhospital mortality and that its predictors differ with age and clinical presentation. The most powerful predictor was previous bleeding. Considering the importance of IHMB, increased efforts are needed to tailor antithrombotic therapy according to age, renal function and other comorbidities.